2000
DOI: 10.1055/s-2000-9269
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Complications With Placenta Previa

Abstract: The purpose of this study is to describe the maternal complications of placenta previa. A population-based retrospective cohort study including all women delivered in the province of Nova Scotia, Canada from 1988 to 1995 was performed. Patient information was obtained from the Nova Scotia Atlee Perinatal Database and maternal complications were described for all women undergoing cesarean delivery. Prognostic factors for the risk of hysterectomy in woman with placenta previa were analyzed by multiple logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
140
5
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(161 citation statements)
references
References 14 publications
8
140
5
8
Order By: Relevance
“…Various studies have shown the incidence of placenta previa ranging from 0.33 to 0.38% of deliveries. 2,6 In the meta analysis reviewing studies on placenta previa between 1950-1996, among 13,992 patients diagnosed with placenta previa the reported incidence of placenta previa ranged from 0.28-2.0% or approximately 1: 200 deliveries.4 This incidence is similar to this study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Various studies have shown the incidence of placenta previa ranging from 0.33 to 0.38% of deliveries. 2,6 In the meta analysis reviewing studies on placenta previa between 1950-1996, among 13,992 patients diagnosed with placenta previa the reported incidence of placenta previa ranged from 0.28-2.0% or approximately 1: 200 deliveries.4 This incidence is similar to this study.…”
Section: Discussionsupporting
confidence: 76%
“…The adverse maternal outcome like postpartum hemorrhage, cesarean hysterectomy, increased need for blood transfusion are dreaded complications. 2,6 Higher risk of preterm birth, low apgar score, congenital malformation increases the perinatal morbidity and mortality.2,7…”
Section: Introductionmentioning
confidence: 99%
“…Crane et al also reported similar complications placenta previa like postpartum haemorrhage (20%), haemorrhagic shock (7%), scar dehiscence 5% and placenta accreta 5% in their study. 14 Surgical management of postpartum haemorrhage was done in 5 cases. In 3 cases bilateral uterine artery ligation and another 2 cases required bilateral internal iliac artery ligation to control postpartum haemorrhage.…”
mentioning
confidence: 99%
“…The need for hysterectomy is significantly increased in PP cases with approximately 30% relative risk. 9 A recent study suggested that a combined ultrasound and clinical scoring model may predict peripartum complication in patients with PP. However, there is a need for more comprehensive and extensive studies for its routine use.…”
Section: Discussionmentioning
confidence: 99%